Specific absorption rate of randomly oriented magnetic nanoparticles in a static magnetic field - Rytov, Ruslan Alekseevich; Usov, Nikolai Aleksandrovich (Beilstein Journal of Nanotechnology, 2023)
Numerical simulations using the stochastic Landau–Lifshitz equation are performed to study magnetization dynamics of dilute assemblies of iron oxide nanoparticles exposed to an alternating (ac) magnetic field with an amplitude Hac = 200 Oe and a frequency f = 300 kHz and a static (dc) magnetic field in the range Hdc = 0–800 Oe. The specific absorption rate (SAR) of the assemblies is calculated depending on the angle between the directions of the ac and dc magnetic fields. For the case of an inhomogeneous dc magnetic field created by two opposite magnetic fluxes, the spatial distribution of the SAR in the vicinity of the field-free point is obtained for assemblies with different nanoparticle size distributions. The results obtained seem to be helpful for the development of a promising joint application of magnetic nanoparticle imaging and magnetic hyperthermia.
Keywords: dynamic hysteresis loop; magnetic hyperthermia; magnetic nanoparticles; magnetic particle imaging; specific absorption rate; static magnetic field